Aeromagnetic Investigation of the Central Apennine Seismogenic Zone (Italy): From Basins to Faults. Issue 5 (17th May 2018) - Minelli, Liliana; Speranza, Fabio; Nicolosi, Iacopo; D'Ajello Caracciolo, Francesca; Carluccio, Roberto; Chiappini, Stefano; Messina, Alfio; Chiappini, Massimo
Abstract: We report on a high‐resolution, low‐altitude aeromagnetic investigation of the central Apennine extensional seismogenic zone, hit by destructive historical earthquakes including the 2009 L'Aquila seismic sequence. Central Apennines are predominantly made by thick (>4 and possibly up to 12 km) packages of shelf and deep marine limestones and dolomites of Mesozoic age, unconformably covered by upper Pliocene‐Holocene continental sediments lying on (often active) normal fault hanging walls. Seismogenic faults cut the carbonates down to 10‐ to 12‐km depth, where the brittle‐ductile transition occurs. Aeromagnetic data were collected during June 2014 with a cesium magnetometer, along 200‐m‐spaced flight lines. Apart from a regional 80‐nT anomaly that we modeled at 30‐ to 40‐km depths in the lower crust of the Adria plate, weak magnetic residuals are observed. As expected, normal faults cutting the diamagnetic carbonates lack any magnetic fingerprint. However, shallow continental basins yield clear anomalies of 2‐ to 8‐nT intensity, as they contain both residual soils and tephra erupted after 0.7 Ma by volcanoes from the Tyrrhenian margin of Italy. Basin margins imaged by aeromagnetism mirror the geometry of their causative normal faults. Thus, aeromagnetic residuals document many of the central Apennine normal faults that were active during the last 3 Ma. Most prominent anomalies reflect basins formed after 0.7 Ma, as their magnetization is significantly higher than that of older continental basins. We conclude that rectilinear boundaries of most prominent anomalies reflect faults formed after 0.7 Ma, thus probably seismogenic. Key Points: High‐resolution aeromagnetic survey was performed to infer on central Apennine seismotectonics High‐frequency magnetics mostly highlight post‐0.7 Ma intermontane continental basins and (active) normal faults bounding them Lower crust of the Adria plate (below Apennine orogenic wedge) is the source of long‐wavelength anomaly